Paternal Perinatal Mental Health: At-Risk Fathers' Perceptions of Help-Seeking and Screening. Issue 3 (October 2019) - Schuppan, Kelly M.; Roberts, Rachel; Powrie, Rosalind
Given the prevalence of paternal perinatal mental health concerns, researchers have suggested introducing routine screening. However, little is known about the acceptability of perinatal screening measures in male populations. Furthermore, the need for screening is influenced by men's perinatal help-seeking behaviors. A thematic analysis of interview data from nine men at risk of paternal perinatal depression and/or anxiety investigated both acceptability of screening and help-seeking behaviors. Themes indicate that routine screening is desired, but acceptability is influenced by perceptions of its intention and possible outcomes. Findings also suggest that barriers to men's perinatal help-seeking are likely to be minimized by increased awareness and normalization. Future research and clinical practice should account for complexities raised by men's perceptions of health care services.